Survey on different polyphenol extraction methods from avocado seed (Persea americana Mill) and assay on their antioxidant and acute toxicity activities. Issue 6 (21st December 2021) - Hue, Ha Thi; Thai, Nguyen Minh; Dao, Phan Thi Anh
Abstract: A comprehensive investigation of extraction methods on the efficiency of the total polyphenol contents (TPC) and antioxidant activities for both avocado seed groups with and without removing antinutrients (signed as groups A and B) and assessing acute toxicity on the extraction products. The Soxhlet extraction showed the most effective method for producing an avocado seed extract possessing the highest TPC and strong antioxidant activities, followed by the maceration, hot extraction, and percolation extraction. Interestingly, it was found that antinutrients containing in the seed can reduce TPC. For instances, sample 4B (Soxhlet method) exhibited the largest TPC (189.67±3.58 mgGAE/g DW) and DPPH inhibitory activity (IC50 = 19.24±1.23 μg/mL), while those of the sample 2A (percolation method) were 68.95±3.79 mgGAE/g DW and 67.48±0.98 μg/mL, respectively. Additionally, sample 4B did not exhibit acute oral toxicity (Dmax = 21.05 g/kg mice weight), indicating a safe and high antioxidant activity of avocado seed extract for clinical applications. A high correlation analyzed by Pearson's correlation was found for the TPC to DPPH assay and ferric reducing/ antioxidant assay, showing their correlation parameters of ‐0.898 and 0.847 (p < 0.05), respectively.